Enriquecimento protéico da farinha de sementes de mangaba (Hancornia speciosa Gomes) através de fermentação em estado sólido - Araújo, Kyzzes Barreto (2011)
The increase concern with the environment is mobilizing various segments of the market for the minimization, recovery and waste of recycling. Over there produce a negative impact on the environment the generation of waste represents a loss of raw material and energy in addition to requiring large investments in treatments to control pollution. The development of bioprocesses emerges as a viable alternative to the use of agro-industrial residues. In this work evaluated the potential of microrganisms Aspergillus oryzae and Rhizopus oryzae for the protein enrichment of mangaba seeds flour by solid state fermentation. The fermentations were performed in petri dishes varying the initial substrate moisture between 24% and 66% and the fermentation temperature between 28ºC and 42°C using DCCR. Increase protein enrichment was obtained with both microorganisms when used initial substrate moisture the 60% and fermentation temperature of 40 ° C. In the fermentation with Aspergillus oryzae was obtained protein increase 7.5 fold of soluble protein, 2.5 fold increase in crude protein and methionine content of 1,6 fold and with Rhizopus oryzae increase protein was 5,0 fold in soluble proteins, 3.2 on crude protein and increased the content of methionine of 2.0 fold. Both microorganisms showed potential for the enrichment of mangaba seeds flour with the advantage of not having had any toxicity for the presence of aflatoxins.